Motivational Orientations of High-Achieving Students as Mediators of a Positive Perception of a High-Achieving Classmate: Results from a Cross-national Study - Oh, Hyerim; Badia-Martín, Maria del Mar; Blumen, Sheyla; Maakrun, Julie; Nguyena, Quoc An-Thu; Stack, Niamh; Sutherland, Margaret; Wormald, Catherine; Ziegler, Albert (Anales de Psicología / Annals of Psychology, 2016)
The purpose of this study was to explore whether and in what ways high-achieving school students’ motivational orientations influence their perceptions of a fictitious future high-achieving classmate. The final sample consisted of the 396 highest achieving students out of a sample from 1794 seventh and tenth graders from five countries: Australia, Peru, South Korea, Spain, and Vietnam. A series of stepwise regression models were used to test the hypothesis that positive perceptions of a high-achieving classmate might be mediated by an approach motivation, but not by an avoidance motivational orientation. The hypothesis was generally confirmed. Learning goal orientation and performance approach motivation predicted positive perceptions of a high-achieving classmate’s intellectual ability, social qualities and popularity among peers, whereas a performance avoidance orientation was usually uncorrelated. However, sporadic exceptions have been found among the participants from Vietnam, South Korea, and Peru.